Shared Neural Substrates of Emotionally Enhanced Perceptual and Mnemonic Vividness - Todd, Rebecca M.; Schmitz, Taylor W.; Susskind, Josh; Anderson, Adam K. (Frontiers in Behavioral Neuroscience, 2013)
It is well known that emotionally salient events are remembered more vividly than mundane ones. Our recent research has demonstrated that such memory vividness is due in part to the subjective experience of emotional events as more perceptually vivid, an effect we call emotion-enhanced vividness, or EEV. The present study built on previously reported research in which fMRI data were collected while participants rated relative levels of visual noise overlaid on emotionally salient and neutral images. Ratings of greater EEV were associated with greater activation in the amygdala, visual cortex, and posterior insula. In the present study, we measured BOLD activation that predicted recognition memory vividness for these same images one week later. Results showed that, after controlling for differences between scenes in low-level objective features, hippocampus activation uniquely predicted subsequent memory vividness. In contrast, amygdala and visual cortex regions that were sensitive to EEV were also modulated by subsequent ratings of memory vividness. These findings suggest shared neural substrates for the influence of emotional salience on perceptual and mnemonic vividness, with amygdala and visual cortex activation at encoding contributing to the experience of both perception and subsequent memory.